Effectiveness of Consumer Dispute Resolution Mechanism Through the Indonesian Consumer Resolution Agency (BPSK) - Nursyahfitri Nursyahfitri; Abdul Halim Nasution; Siti Annisa Br. Nainggolan; Deva Anggraini; Sasna Safitri; Dinda Selpiyani; Devina Natasya; Sastia Putri Br. Ginting; Della Annisa Putri (Fox Justi : Jurnal Ilmu Hukum, 2026)
Study This aiming For analyze effectiveness mechanism settlement dispute consumer through the settlement body Consumers (BPSK) Indonesia. Research This use method study law bibliography , namely research conducted​ with method researching ingredients library or secondary data . Research This aiming For give understanding deep about phenomenon certain without do research field . Settlement Agency Dispute Consumers (BPSK) have role crucial in provide mechanism settlement dispute consumers outside​ court , through three method main : conciliation , mediation , and arbitration . Conciliation nature passive , where the assembly only facilitate agreement of the parties which then poured out in agreement peace . In overall , although BPSK was designed For give justice for consumers , various constraint structural , source power , and especially inconsistency regulation related strength law the verdict hinder effectiveness and certainty the law .